Diverticulitis perforada: alternativas de manejo quirúrgico. Caso clínico y revisión de literatura - Pereira C., Nicolás; Vega S., Javier; Readi V., Alejandro; Abedrapo M., Mario (Revista Hospital Clínico Universidad de Chile, 2012)
Sigmoid diverticular disease is common in the occidental world and it is responsible for a great number of hospitalizations. The prevalence of diverticular disease increases with age and only in few cases it is manifest as diverticulitis. Diverticulitis produces variable clinical manifestations, ranging from simple inflammation that only requires medical management, to a life threatening condition, due to a free perforation that requires urgent surgical management. Surgical management is recommended after the first attack of complicated diverticulitis, due to the elevated rate of recurrence after successful medical treatment. In this article we presenta clinical case of complicated diverticulitis with free perforation treated with laparoscopic peritoneal lavage, and we make a review of the different surgical alternatives, such as Hartmann’s operation, resection with primary anastomosis and laparoscopic peritoneal lavage.